NATIONALISM INSIDE THE POEM OF â€œDIPONEGOROâ€ BY CHAIRIL ANWAR A HISTORICAL STUDY - Djojosuroto, Kinayati (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2014)
This study aims to reveal the meaning of the elements of nationalism in the poem